Coverage of different health insurance programs and medical costs associated with chronic hepatitis C infection in mainland China: a cross-sectional survey in 20 provinces. Issue 1 (December 2016) - Zhou, Hai-yang; Liu, Shuang; Zheng, Su-jun; Peng, Xiao-xia; Chen, Yu; Duan, Carol; Zheng, Qing-fen; Wang, Zhao; Duan, Zhong-ping
Abstract Background Hepatitis C virus (HCV) imposes a considerable disease burden in China, with at least 10 million people chronically infected. Little is known about the financial impact of the HCV epidemic, nor about the extent to which various forms of insurance are providing HCV patients with financial protection. A cross-sectional multi-site study was conducted to acquire data that will aid policy-makers and other stakeholders in developing effective strategies to address this situation. Methods At 29 hospitals across China, inpatients and outpatients with chronic HCV were surveyed about their insurance coverage and medical costs. Percentages, means and medians were calculated, and differences in continuous variables among multiple groups were analyzed using the Kruskal-Wallis test or Wilcoxon two-sample test. Results Many inpatients (N = 593) and outpatients (N = 523) reported being covered by one of three major types of government health insurance, but 13 % of inpatients and 43 % of outpatients reported having no insurance. Among inpatients, the total median cost per hospitalization per patient was 8212 Renminbi (RMB). The category of expenditure with the highest median cost per hospitalization was Western medicine, followed by lab tests and Chinese medicine. The median cost per hospitalization was far higher for patients who had hepatocellular carcinoma than for those with less severe forms of liver disease. Outpatient antiviral therapy costs ranged from a median of 377 RMB for ribavirin to a median of 37, 400 RMB for pegylated interferon-alpha for up to one year of treatment. Conclusions For uninsured chronic HCV patients in China, inpatient and outpatient costs may be financially devastating. Research is needed on how different approaches to financing HCV treatment and care might improve health outcomes as well as achieve cost savings by enabling more people to be cured of HCV.